A conceptual framework of implementing lean communication for building back better in the post-disaster housing reconstruction - Lalan Helny; Suraji Akhmad; Ophiyandri Taufika; Hidayat Benny (E3S Web of Conferences)
In the aftermath of disasters, effective communication plays a pivotal role in facilitating efficient and sustainable housing reconstruction efforts. This paper proposes a conceptual framework to explore the application of lean communication principles in the context of post-disaster housing reconstruction. The framework integrates theories from lean management studies and communication to enhance our understanding of how lean principles can optimize communication processes among stakeholders involved in housing reconstruction. By adopting a qualitative approach, this study aims to develop a framework to identify key communication challenges and opportunities and to examine existing practices for implementing lean communication strategies to achieve the goal of building back better. The theoretical contribution of this framework lies in its potential to inform policymakers, practitioners, and researchers about the importance of lean communication in promoting resilience and sustainability in post-disaster housing reconstruction initiatives.